Characterization of the EM66 Biomarker in the Pituitary and Plasma of Healthy Subjects With Different Gonadotroph Status and Patients With Gonadotroph Tumor - Guillemot, Johann; Guérin, Marlène; Cailleux, Anne-Françoise; Lopez, Antoine-Guy; Kuhn, Jean-Marc; Anouar, Youssef; Yon, Laurent (Frontiers in Endocrinology, 2019)
Granins and their derived-peptides are useful markers of secretion from normal and tumoral neuroendocrine cells. The need to identify new diagnostic markers for neuroendocrine tumors, including pituitary tumors prompted us to determine plasma levels of the secretogranin II-derived peptide EM66 in healthy volunteers with different gonadotroph status and to evaluate its usefulness as a circulating marker for the diagnosis of gonadotroph tumor. Using a radioimmunoassay, we determined plasma EM66 concentrations in healthy men and women volunteers in different physiological conditions in relation with the gonadotroph function. Our results revealed that in men, in women with or without contraception, in pregnant or post-menopausal women, plasma EM66 concentrations are not significantly different, and did not show any correlation with gonadotropin levels. In addition, stimulation or inhibition tests of the gonadotroph axis had no effect on EM66 levels, whatever the group of healthy volunteers investigated while gonadotropin levels showed the expected variations. Immunohistochemical experiments and HPLC analysis showed the occurrence of EM66 in pituitary gonadotroph, lactotroph and corticotroph tumors but not in somatotroph tumor. In patients with gonadotroph or lactotroph tumor, plasma EM66 levels were 1.48 (0.82–4.38) ng/ml and 2.49 (1.19–3.54) ng/ml, respectively. While median value of EM66 was significantly lower in patients with gonadotroph tumor compared to healthy volunteers [2.59 (0.62–4.95) ng/ml], plasma EM66 concentrations were in the same range as normal values and did not show any correlation with gonadotropin levels. These results show that plasma EM66 levels are independent of the activity of the gonadotroph axis in healthy volunteers and, while EM66 levels are reduced in gonadotroph tumors, plasma EM66 does not provide a helpful marker for the diagnosis of these tumors.